Pengaruh Service Quality, Social Media Promotion dan Online Customer Review Terhadap Repeat Purchase di PO Rimba Raya Jepara - Awwaludin Amri , M. Daffa; Ali, Ali (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2024)
Transportation within a country is becoming increasingly important due to the impact of globalization which encourages life to be more competitive. All caused by the emergence of Covid-19 which accelerated digitalization. The aim of the research is to determine the influence of studies that focus on service quality variables, social media promotions, online customer reviews on repeat purchases at PO. Rimba Raya Kabupaten Jepara. The validity and reliability tests were obtained using a Likert scale, namely an open questionnaire. This study took 167 samples, using a purposive sampling technique, using the Slovin formula as a guide. The exact population size is not known. The data analysis process uses the PLS-SEM SmartPLS version 4.0 method. The results of this research show that service quality and social media promotions do not have a significant effect, while online customer reviews have a significant effect on repeat purchases.